Urinalysis: Extract the Relevant Information Before Throwing it into the Drain - Lamsal, Madhab (Annals of Clinical Chemistry and Laboratory Medicine, 2021)
From ancient time urine has been considered as a substance of importance and examination for physical wellbeing. Evidences from the ancient civilizations including the Egyptian, Sumerian, Babylonian and Eastern Civilizations such as Vedic cultures support the use of urine as an index of physical and mental well-being. Classified as coloured, black, frothy, cloudy and sweet, urine used to be correlated with different disease conditions such as jaundice, kidney diseases, diabetes etc. These practices have been carried on even by the alchemists and have now formed as an integral constituent of clinical laboratory diagnostics. Modern approach to urinalysis can be credited to Dr. Richard Bright, MD, who in 1827 by performing urine examinations related to vol-ume, colour, pH, protein (but not cast) corre-lated his findings to several diseases and clini-cal picture including edema, proteinuria etc. Urinalysis combines the expertise from vari-ous disciplines including biochemistry, pa-thology, microbiology, cytology etc. Urinalysis may be used for screening, diagnosis, monitoring and prognosis due to the ease of collection in any settings. Modern day tech-niques such as molecular biology, immunolo-gy, and mass spectrometry with high resolu-tion microscopy have taken up urinalysis to explore the genetic predisposition to inherited diseases and tumor studies besides the routine diagnostics. So, variation occurs in urinalysis from the simple routine analysis, microscopic examination to highly sophisticated and ad-vanced automated analytical techniques. Uri-nalysis therefore, forms a key component of personalized medicine also integrating with proteomics, genomics, metabolomics approaches.